Selected letters of Margaret Laurence and Adele Wiseman - Laurence, Margaret; Wiseman, Adele (University of Toronto Press, 1997)
"Over a period of forty years, from 1947 to 1986, Margaret Laurence and Adele Wiseman wrote to each other constantly. The topics they wrote about were as wide-ranging as their interests and experiences, and their correspondence encompassed many of the varied events of their lives. Laurence's letters - of which far more are extant than Wiseman's - reveal much about the impact of her years in Africa, motherhood, her anxieties and insecurities, and her development as a writer. Wiseman, whose literary success came early in her career, provided a sympathetic ear and constant encouragement to Laurence." "The editors' selection has been directed by an interest in these women as friends and writers. Their experiences in the publishing world offer an engaging perspective on literary apprenticeship, rejection, and success. The letters reveal the important role both women played in the buoyant cultural nationalism of the 1960s and 1970s." "This valuable collection of previously unpublished primary material will be essential to scholars working in Canadian literature and of great interest to the general reading public."--Jacket.